1987
DOI: 10.1007/bf02623492
|View full text |Cite
|
Sign up to set email alerts
|

bFGF is the putative natural growth factor for human melanocytes

Abstract: Normal human melanocytes, unlike pigment cells from metastatic melanomas, do not survive in culture in routine, serum-supplemented media. The search for natural growth factors for melanocytes has shown that mitogenic activity is ubiquitous in several tissues and in melanomas. Of several known growth factors tested, basic fibroblast growth factor (bFGF) was the only one mitogenic for melanocytes but only in the presence of cyclic-adenosine-monophosphate (cAMP) stimulators. The mitogenic activity toward melanocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
252
3
4

Year Published

1991
1991
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 284 publications
(270 citation statements)
references
References 26 publications
11
252
3
4
Order By: Relevance
“…The autocrine growth of melanoma cells is conferred, at least in part, by ectopic expression of growth factors (Balentien et al, 1991;Easty et al, 1995;Halaban, 1992). Of all the melanocyte growth factors listed above, bFGF (basic FGF) plays the most decisive role in the progression of normal human melanocytes to melanomas (Becker et al, 1989(Becker et al, , 1992Halaban et al, 1987Halaban et al, , 1988Halaban et al, , 1991. The abnormal expression of bFGF/FGF2 is detected already in melanocytes in atypical nevi in situ (Albino et al, 1991;Reed et al, 1994;Scott et al, 1991), and has been observed in all melanoma cell lines tested.…”
Section: Introductionmentioning
confidence: 99%
“…The autocrine growth of melanoma cells is conferred, at least in part, by ectopic expression of growth factors (Balentien et al, 1991;Easty et al, 1995;Halaban, 1992). Of all the melanocyte growth factors listed above, bFGF (basic FGF) plays the most decisive role in the progression of normal human melanocytes to melanomas (Becker et al, 1989(Becker et al, , 1992Halaban et al, 1987Halaban et al, , 1988Halaban et al, , 1991. The abnormal expression of bFGF/FGF2 is detected already in melanocytes in atypical nevi in situ (Albino et al, 1991;Reed et al, 1994;Scott et al, 1991), and has been observed in all melanoma cell lines tested.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in combination with ultraviolet radiation, bFGF has been shown to act as a potent inductor of melanoma (Berking et al, 2001). In contrast to melanocytes, bFGF can be produced by nevus and melanoma cells and may act as an autocrine growth factor through the FGF receptors (Halaban et al, 1987;Halaban et al, 1988c;Albino et al, 1991;Scott et al, 1991;Reed et al, 1994;al-Alousi et al, 1996a, b;Meier et al, 2003). It has been demonstrated that melanoma cells cannot survive if bFGF or FGFR1 are targeted (Wang and Becker, 1997;Graeven et al, 2001;Valesky et al, 2002).…”
mentioning
confidence: 99%
“…Un candidat potentiel était FGF2 ou bFGF (basic fibroblast growth factor). FGF2 est un facteur de croissance soluble impliqué dans la prolifé-ration, la différenciation, la survie et le chimiotactisme des mélanocytes [5][6][7][8]. Effectivement, les auteurs montrent que l'expression de FGF2 est plus importante dans les cultures de kératinocytes éta-blies à partir des souris Krt5-Foxn1 que les souris sauvages.…”
Section: Magazineunclassified